Novel Patch for Transdermal Administration of Morphine - Inui, Naoki; Kato, Tatsuhisa; Uchida, Shinya; Chida, Kingo; Takeuchi, Kazuhiko; Kimura, Takahito; Watanabe, Hiroshi (Journal of Pain and Symptom Management, 2012)
Transdermal absorption of morphine into the systemic circulation through intact skin has not been reported. To describe a novel transdermal formulation for a morphine hydrochloride patch consisting of polyethylene sponge foam as the retaining agent and adjusted proportions of morphine hydrochloride and adjunctive drugs. In this study, the transdermal morphine hydrochloride patch was administered to intact skin in five subjects and the plasma concentrations of morphine and its metabolites were examined. Morphine was absorbed systemically, producing plasma morphine concentrations above the assay detection limit by at least 24 hours after attachment of patches containing a total dose of 180mg of morphine. The levels gradually increased in a time-dependent manner without serious events. The area under the concentration-time curve from 0 to 72 hours (AUC0–72) values for morphine, morphine-6-glucuronide, and morphine-3-glucuronide were 60.4±13.4, 133.7±17.4, and 861.5±126.7ng·h/mL, respectively. The mean plasma area under the concentration-time curve from 0 to 72 hours ratio for morphine-6-glucuronide relative to morphine was 2.64. These data provide useful information for developing a transdermal morphine system.